2019
DOI: 10.1177/2325967119s00088
|View full text |Cite
|
Sign up to set email alerts
|

Acl Growth With Age in Pediatric Patients: An Mri Study

Abstract: Background The incidence of anterior cruciate ligament (ACL) injury is steadily increasing in skeletally immature patients [1-7]. As a result, surgical approaches to reconstruction of the ACL without compromising the physis have been developed [6, 8, 9]. It is essential to understand how the native ACL changes with patient growth and age, in order to better understand how grafts might serve patients as they continue to grow. The purpose of this study is to characterize the morphological change over time of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…However, the posterior cruciate ligaments thickness increased with age having a greater thickness at old age than at ayoung age. This finding is consistence with the findings of recent studies [9,10]. Infact, Iriuchishimaet al, [9] reported that 'the anterior cruciate ligament areas on the sagittal plane were significantly larger in the younger age group when compared to the elderly age group' similar to the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the posterior cruciate ligaments thickness increased with age having a greater thickness at old age than at ayoung age. This finding is consistence with the findings of recent studies [9,10]. Infact, Iriuchishimaet al, [9] reported that 'the anterior cruciate ligament areas on the sagittal plane were significantly larger in the younger age group when compared to the elderly age group' similar to the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The posterior cruciate ligament showed marked growth especially at the femoral end compared to the anterior cruciate ligaments. This is consistent with a related study that reported that ACL grows in thickness until the age of 18years [10]. The earlier study revealed that ACL thickness showed an average of 0.22 mm of growth per year between 1.5 and 18.75 years old with growth completed by age 18.75 years and subsequent decrease in diameter at a later age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation